2012
DOI: 10.4049/jimmunol.1102693
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epidermal Growth Factor Receptor Tyrosine Kinase Ameliorates Collagen-Induced Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune synovitis characterized by the formation of pannus and the destruction of cartilage and bone in the synovial joints. Although immune cells, which infiltrate the pannus and promote inflammation, play a prominent role in the pathogenesis of RA, other cell types also contribute. Proliferation of synovial fibroblasts, for example, underlies the formation of the pannus, while proliferation of endothelial cells results in neovascularization, which supports the growth of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
1
46
0
1
Order By: Relevance
“…Increasing evidence shows that EGFR contributes to the pathogenesis of RA by modifying the pathological environment, such as cytokine production or angiogenensis, and inhibition of EGFR tyrosine kinase activity ameliorates collagen-induced arthritis. 30,31 Of interest, treatment with conditioned medium of miR-573 mimic transfected RASFs could inhibit angiogenic ability of HUVECs, indicating that miR-573 also mediated the interaction between RASFs and its surrounding cells. In this study, silencing EGFR did not reduce the production of cytokines or invasion of RASFs, but down-regulated VEGF secretion in the conditioned medium, thereby inhibiting the proangiogeneic ability of HUVECs after concurrent transfection with miR-573 inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence shows that EGFR contributes to the pathogenesis of RA by modifying the pathological environment, such as cytokine production or angiogenensis, and inhibition of EGFR tyrosine kinase activity ameliorates collagen-induced arthritis. 30,31 Of interest, treatment with conditioned medium of miR-573 mimic transfected RASFs could inhibit angiogenic ability of HUVECs, indicating that miR-573 also mediated the interaction between RASFs and its surrounding cells. In this study, silencing EGFR did not reduce the production of cytokines or invasion of RASFs, but down-regulated VEGF secretion in the conditioned medium, thereby inhibiting the proangiogeneic ability of HUVECs after concurrent transfection with miR-573 inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent article, Deng et al (1) confirmed that leptin, a peptide hormone produced by adipose tissue, increases the Th17 response and contributes to disease progression in mice with collagen-induced arthritis (2). In vitro data also showed that leptin treatment significantly enhanced Th17 cell generation from naive CD4ϩ T cells.…”
Section: To the Editormentioning
confidence: 58%
“…The EGFR pathway plays an important role in the pathophysiology of cancer (Normanno et al, 2006), cardiovascular disease (Nakata et al, 1996;Reape et al, 1997;Asakura et al, 2002;Kagiyama et al, 2002;Flamant et al, 2003), psoriasis (Sergi et al, 2000;Overbeck and Griesinger, 2012), arthritis (Hallbeck et al, 2005;Swanson et al, 2012), and experimental chronic kidney disease (Terzi et al, 2000;Lautrette et al, 2005;Liu et al, 2012). Therapeutic drugs targeting this pathway have potential to treat diverse human diseases in addition to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…All of the current drugs that target the EGFR for cancer are associated with a pustulant purulent skin rash predominantly on the face, neck, shoulder, and back, occurring in up to 85% of patients (Li and Perez-Soler, 2009). The EGFR pathway has also been implicated but less well-studied in other diseases, such as atherosclerosis (Nakata et al, 1996;Reape et al, 1997), hypertension (Kagiyama et al, 2002;Flamant et al, 2003), left ventricular hypertrophy (Asakura et al, 2002), arterial remodeling (Taylor et al, 1999), psoriasis (Sergi et al, 2000;Overbeck and Griesinger, 2012), arthritis (Hallbeck et al, 2005;Swanson et al, 2012), chronic obstructive pulmonary disease (COPD) (Cockayne et al, 2012), asthma (Zhen et al, 2007), and chronic kidney disease (CKD) (Terzi et al, 2000;Lautrette et al, 2005;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%